Prevalencia de neuromitos y conocimiento general de neurociencias en la comunidad académica de una universidad de Ecuador (Investigaciones) - Flores Ferro, Elizabeth (2024)
Neuroscience corresponds to a group of disciplines that study the nervous system. A lack of understanding of them, combined with their indiscriminate application in education, has led to a series of misconceptions about the brain, giving rise to neuromyths. Objective: The aim of this study was to describe and compare the prevalence of neuromyths and the general knowledge of neuroscience among members of an educational community of students and teachers from a Higher Education Institution in Ecuador. Methodology: Quantitative, non-experimental cross-sectional. The sample consisted of 203 students and teachers from a Higher Education Institution in Ecuador. Dekker’s Neuromyth Prevalence Questionnaire was used. Results: The most entrenched neuromyths in the sample were those associated with coordination exercises and their relationship with language, VAK learning styles, and enriched environments in the preschool stage. Conclusions: It is necessary to promote the exchange of best practices to develop pathways with training adequate for the development of competencies that higher education teachers require in the field of neuroscience.